Patients’ perception on stressful events for fibromyalgia development - Ana Julia Campi Nunes de Oliveira; Thaís Di-Giovanni; Cassiano Henrique Giovanini Vanzelli; Bruno de Mendonça Moraes Araujo; Reinaldo José Gianini; José Eduardo Martinez (BrJP, 2024)
BACKGROUND AND OBJECTIVES: Fibromyalgia syndrome (FM) is a rheumatic disease with the following characteristics: generalized chronic pain, fatigue, non-restorative sleep and cognitive disturbances. It is often associated to distress followed chronic and acute stressors exposures. The objective of this study was to determine the patients’ perception if stressful events influence the development of FM. The secondary objective was to evaluate the impact of acute stress in determining the future severity of FM. METHODS: A cross-sectional study was carried out for the primary objective and a case-control study for the secondary objective. We used questionnaires on demographic data and instruments for assessing the severity and impact of FM (Fibromyalgia Index - FI, and Revised Fibromyalgia Impact Questionnaire - FIQr), instruments for assessing emotional aspects (PHQ-9 and GAD-7), and a questionnaire on patients’ perception of stressful events. RESULTS: Sixty-one patients were evaluated. About 59% reported the presence of acute stress as an aggravating factor. Patients mentioned grief for a close relative, financial problems, family conflicts, and being a victim of violence as aggravating events. There was a significant association between the presence of stressful incidents, FI and FIQr (p<0.05). The presence of aggravating circumstances increased the FIQr score by 2.72. CONCLUSION: It was observed a significant association between aggravating stressful events and higher index FM scores and their impact on the patients.